2021
DOI: 10.7717/peerj.11463
|View full text |Cite
|
Sign up to set email alerts
|

Coupling effects of phosphorus fertilization source and rate on growth and ion accumulation of common bean under salinity stress

Abstract: Many agricultural regions in arid and semiarid climate zone need to deal with increased soil salinity. Legumes are classified as salt-sensitive crops. A field experiment was performed to examine the application of phosphorus (P) fertilizer source and rate on growth, chlorophylls and carotenoid content, DNA and RNA content and ion accumulation in common bean (Phaseolus vulgaris L.) cultivated under salinity stress. An experimental design was split-plot with three replicates. The main plots included two P source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…The following is an explanation of how the administration of P stimulates the buildup of Na + in the vacuole: Both H + adenosine triphosphatase and pyrophosphatase pumps acidify the inside of the vacuole with H + , prompting the H + /Na + antiport protein to substitute the cytosol's Na + with the vacuole's H + [73]. Similar to our results, Roy et al [24], Ahmad et al [23], de Andrade et al [25], and Mohamed et al [26] reported that P or Ca 2+ supplements improved the crops' resistance to soil salinity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The following is an explanation of how the administration of P stimulates the buildup of Na + in the vacuole: Both H + adenosine triphosphatase and pyrophosphatase pumps acidify the inside of the vacuole with H + , prompting the H + /Na + antiport protein to substitute the cytosol's Na + with the vacuole's H + [73]. Similar to our results, Roy et al [24], Ahmad et al [23], de Andrade et al [25], and Mohamed et al [26] reported that P or Ca 2+ supplements improved the crops' resistance to soil salinity.…”
Section: Discussionsupporting
confidence: 90%
“…Calcium and phosphorus are essential macronutrients for plant metabolic processes and vital macromolecules. They are documented to alleviate the harmful effects of soil salinization on tomato [23], rice [24], sweetsop [25], and common bean [26]. However, excessive P and Ca fertilizers use causes many problems such as micronutrient imbalance, leaching, groundwater contamination, and eutrophication [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Salinity stress severely disturbs plant growth via various physiological processes ( Mujeeb-Kazi et al., 2019 ; Saddiq et al., 2019 ; Saddiq et al., 2020 ). Salinity affected wheat growth parameters via decreased water availability and increased levels of Na and Cl ions which interfered with essential macro elements such as Mg, K, and Ca uptake from the soil, thus resulting in nutrient deficiency ( Awad et al., 2012 ; Saddiq et al., 2019 ; Saddiq et al., 2020 ; Mohamed et al., 2021 ). Also, ion toxicity and the osmotic stress caused by high salt concentrations caused an imbalance in crucial metabolic processes due to oxidative stress ( Chinnusamy et al., 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…This can be attained by generating the latest adaptable varieties with higher yield potential and applying appropriate agricultural practices ( Abdelhamid et al., 2003 ; Abdelhamid et al., 2011 ; El Sabagh et al., 2021 ). These practices includes applications of biofertilizers, mineral fertilizer as a source of phosphorus and potassium ( Dawood et al., 2014 ; Mohamed et al., 2021 ), inoculation of an exopolysaccharides (EPS) producing bacterial strains ( Awad et al., 2012 ), as well as using various naturally occurring compounds as exogenous plant treatment such as vitamins, antioxidants, amino acids, etc. The application of amino acids is one of these approaches used to increase plant productivity in sub-optimal conditions ( Abd Elhamid et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the increase in P levels stimulated the N 2 fixation efficiency and N uptake in lentils by improving active nodules and their dry weight plant −1 (Jindal et al, 2008;Rasheed et al, 2010). Mohamed et al (2021) have also disclosed that increasing the P level boosted the root dry weight and absorption of macronutrients in common bean.…”
Section: Discussionmentioning
confidence: 99%